Alguns dos efeitos possíveis da ascensão econômica chinesa para o Brasil e para a região Nordeste - Silva, Iago Nunes da (2024)
This research seeks to understand the historical and social conditions that shaped the economic formation of the northeast and Brazil. The historical analysis of this formation is important for characterizing the structural limitations of this region in international capitalism, as well as its relations with other Brazilian regions located in a global economic periphery. Based on the theoretical explanation of dependence, based mainly on the works of Celso Furtado and Caio Prado Júnior, macroeconomic data related to trade and investments involving relations between China and Brazil and later the northeast and China will be analyzed. Despite using a broader historical period to understand the economic structure of the northeast, the time frame to be explored in more depth is the period that extends from 2000 to 2022. In a first approximation, the conclusion is that the northeast is favored in comparison to other regions of Brazil in the period analyzed. Fundamental data on regional and individual income, profits and wages; expansion of employment and productive capacity in the Northeast are reserved for future research.